Combinatorial fabrication of composite nanorods using oblique angle co-deposition. (2nd August 2016) - Larson, Steven; Huang, Weijie; Zhao, Yiping
Abstract: We demonstrate that oblique angle co-deposition can be used as a versatile combinatory nanofabrication technique to generate a library of nanomaterials. Using the Cu-Fe2 O3 system as an example, by carefully characterizing the vapor plumes of the source materials, a composition map can be generated, which is used to design the locations of all the substrate holders. The resulting nanostructures at different locations show different thickness, morphology, crystallinity, composition, as well as inhomogeneity in microstructures, and material maps of all these structural parameters are established. By further oxidizing or reducing the composite nanostructures, their properties—such as band gap, photocatalytic performance, and magnetic properties—can be easily linked to their composition and other structural parameters. Optimal materials for photocatalytic and magnetic applications are efficiently identified. It is expected that oblique angle co-deposition and its variations could become the most powerful combinatory nanofabrication technique for nanomaterial survey.